2008
DOI: 10.1007/s10863-008-9126-1
|View full text |Cite
|
Sign up to set email alerts
|

Long chain fatty acyl-CoA modulation of H2O2 release at mitochondrial complex I

Abstract: Complex I is responsible for most of the mitochondrial H(2)O(2) release, low during the oxidation of the NAD linked substrates and high during succinate oxidation, via reverse electron flow. This H(2)O(2) production appear physiological since it occurs at submillimolar concentrations of succinate also in the presence of NAD substrates in heart (present work) and rat brain mitochondria (Zoccarato et al., Biochem J, 406:125-129, 2007). Long chain fatty acyl-CoAs, but not fatty acids, act as strong inhibitors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…However, the results of Zoccarato's group (58,59,67,85) revealed that these assumptions are incorrect since the co-presence of glutamate plus malate does not impede H 2 O 2 generation by low succinate but rather acts to enhance H 2 O 2 production and when glutamate plus malate and succinate are all being oxidized together, electrons from glutamate plus malate are still continuing to move through Complex I (because Complex I still continues oxidizing NADH making NAD + available for further 2-OG oxidation). Therefore, it appears likely that the succinate-promoted H 2 O 2 production is a direct consequence of the succinate-dependent elevation of the mitochondrial UQH 2 /UQ ratio and perhaps, to a lower extent, of the reduced level of the Complex I flavin.…”
Section: Resolving the Enigma Of Reverse Electron Flow And Ros Producmentioning
confidence: 96%
See 2 more Smart Citations
“…However, the results of Zoccarato's group (58,59,67,85) revealed that these assumptions are incorrect since the co-presence of glutamate plus malate does not impede H 2 O 2 generation by low succinate but rather acts to enhance H 2 O 2 production and when glutamate plus malate and succinate are all being oxidized together, electrons from glutamate plus malate are still continuing to move through Complex I (because Complex I still continues oxidizing NADH making NAD + available for further 2-OG oxidation). Therefore, it appears likely that the succinate-promoted H 2 O 2 production is a direct consequence of the succinate-dependent elevation of the mitochondrial UQH 2 /UQ ratio and perhaps, to a lower extent, of the reduced level of the Complex I flavin.…”
Section: Resolving the Enigma Of Reverse Electron Flow And Ros Producmentioning
confidence: 96%
“…More recent evidence suggests that long-chain fatty acyl-CoAs also directly inhibit ROS production by inhibiting mitochondrial matrix enzyme complexes (58). Thus, long-chain fatty acyl-CoAs, but not FFAs, acted as strong inhibitors of succinate-dependent H 2 O 2 release.…”
Section: Fatty Acyl Coa Derivatives Inhibit Sdh/complex II Ros Producmentioning
confidence: 98%
See 1 more Smart Citation
“…Complex II itself is not a source of significant radical formation (as seems to hold true for ETF:CoQ reductase and glycerol-3-phosphate dehydrogenase, as described below) but 'activates' complex I [5,6]. The same group also showed succinate activation of radical formation to be suppressed by long chain FA acylCoAs [13]. This seems surprising as levels of FADH 2 could possibly rise even further under these circumstances, but is easily explained by the fact that these compounds are not found to be oxidized under these conditions and, furthermore, they uncouple the isolated mitochondria due to their hydrophobicity.…”
Section: Experimental Support For the Kinetic Modelmentioning
confidence: 89%
“…The crucial extra complication, however, is that more electrons entering complex I with less acceptors available (a high CoQH 2 /CoQ ratio), would lead to 'electron spill'. In isolated mitochondria, reverse electron transport (RET) is involved [13,14]. Radical formation taking place inside a 'proto mitochondrial' cell instead of peripherally, as occurring in bacterial respiration, only makes matters much worse.…”
Section: Mitochondriamentioning
confidence: 99%